Early-career researchers at the 15th DACH Permafrost Conference - K. Schwarzkopf; K. Schwarzkopf; K. Jaspers; K. Jaspers; M. Rometsch; M. Rometsch; K. Wagner; T. Wiegand (Polarforschung, 2025)
In January 2025, for the 15th time, the DACH Permafrost Union (Arbeitskreis Permafrost) held its regular conference. Hosted by the WSL Institute for Snow and Avalanche Research (SLF), the 3 d event in Davos, Switzerland, brought together scientists working on polar and mountain permafrost. The large number of participants, and especially of young researchers, reflects the importance of the DACH Permafrost Conference, not just due to the various scientific contributions but also for workshops, field trips, and social gatherings. Five early-career scientists received financial support from the German Society of Polar Research (DGP) to present their projects and outcomes as posters and talks and to exchange with the broad permafrost community.